Ethnic study of traditional use of Cuayote (Gonolobus taylorianus) in Costa Rica - Rojas Salas, María Fernanda (2020)
The cuayote (Gonolobus taylorianus) is a very unknown, endemic plant from the Central America zone. In Costa Rica, two species of the genus Apocynaceae, Gonolobus edulis and Gonolobus taylorianus are known by the popular name of cuayote. The fruit of both species is traditionally used for food purposes. A medicinal use of the plant and the fruit have also been reported for the treatment of warts and prostate. The fruit characterization revealed, through a phytochemical screening, the presence of important compounds such as flavonoids, steroids, triterpenes, carbohydrates and cardiotonic glycosides